Defect repairing and stabilizing method of carbon-based sodium storage material

By using the treatment method of aromatic ketone sodium and dopamine salt in carbon-based sodium storage materials, the trap effect and solid electrolyte interface formation problems caused by defects in carbon-based materials are solved, and the first week of Coulombic efficiency and cycle of sodium ion batteries are significantly improved. stability.

CN119517943APending Publication Date: 2025-02-25SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311071187.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Defects in carbon-based materials lead to trap effect and solid electrolyte interface formation, resulting in low first-week Coulomb efficiency and poor cycle stability of sodium ion batteries.

Method used

By reacting carbon-based sodium storage material with aromatic ketone sodium solution, impurity defects are compensated and metallossil is formed, and carbonyl active sites are implanted on the surface of the carbon-based negative electrode by self-polymerization of dopamine salts, catalyzing preferential reduction of salts Uniform and dense growth of solid electrolyte interface (SEI).

Benefits of technology

It significantly improves the first week of the Coulomb efficiency and cycle stability of the carbon-based negative electrode, inhibits the sub-decomposition reaction of the electrolyte on the carbon surface, and realizes the practical development of the long-life sodium ion battery system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517943A_ABST
    Figure CN119517943A_ABST
Patent Text Reader

Abstract

The invention relates to a defect repairing and stabilizing method of a carbon-based sodium storage material. The defect repairing and stabilizing method of the carbon-based sodium storage material comprises the following steps: carrying out primary reaction on the carbon-based sodium storage material or a negative electrode containing the carbon-based sodium storage material and an aromatic ketone sodium solution, then carrying out secondary reaction with a dopamine salt solution, and finally washing and drying to obtain the modified carbon-based sodium storage material or the modified negative electrode containing the carbon-based sodium storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for pretreating a carbon-based sodium storage material, and the obtained negative electrode and sodium ion battery, and belongs to the field of electrochemical energy storage and new energy. Background Art

[0002] The development of advanced sodium-ion batteries depends on the construction of high-performance electrode materials, and the development of low-cost, high-performance negative electrode materials is a key link. Due to their abundant reserves, low cost, stable structure and low sodium insertion voltage platform, carbon-based materials such as hard carbon, soft carbon and graphite have attracted widespread attention, among which hard carbon has become a negative electrode material with commercial prospects. Theoretical and experimental evidence shows that defects are crucial to the high reversible capacity of carbon negative electrodes. There are two main types of defects in hard carbon, intrinsic defects and impurity defects. Intrinsic defects include vacancies, holes and edges on nanosheets, which are mainly composed of dangling bonds and sp3 hybridized carbon with other structural branches. Pentagons, heptagons, octagons and their combination with several non-hexagonal structures (such as StoneThrower Wales defects) lead to bending of graphene nanosheets, which are also intrinsic defects. Impurity defects mainly refer to inhomogeneous atoms, the most common of which are oxygen-containing functional groups, which usually appear in vacancies and edges. Defects in hard carbon anodes play an important role in high-capacity sodium storage, however, defects also have some negative effects that cannot be ignored, especially the trap effect and the solid electrolyte interface (SEI) that produces irreversible capacity. Therefore, the irreversible sodiumization of defects and the formation of the solid electrolyte interface (SEI) during the first charge and discharge process of hard carbon consume a large amount of active sodium ions, thereby reducing the first coulombic efficiency (ICE) and cycle stability of the hard carbon anode.

[0003] In the literature Carbon 2018, 129, 695-701, researchers used hydrogen to reduce the defect concentration of hard carbon, and the ICE increased from 65% to 79%. The literature Nano Energy 2019, 64, 103937 reported a new in-situ engineering method to adjust the residual oxygen atoms / defects of hard carbon by controlling the atmosphere of the pyrolysis synthesis process, and revealed the important correlation between ICE and residual oxygen atoms / defects. When used as the anode of a sodium ion battery, the hard carbon electrode with reduced residual oxygen atoms and defects can achieve a high average ICE of more than 85%, which is much higher than the ICE value of ~70% commonly observed for the original hard carbon electrode. In addition, in addition to regulating defects during the preparation of hard carbon, in order to improve the reversible cycle capacity and first coulombic efficiency of the hard carbon negative electrode, people have developed pre-sodiumization technology for carbon materials, including direct sodium supplementation with metallic sodium, short-circuit pre-sodium method, and three-electrode pre-sodium method. Although metallic sodium has a significant improvement effect, the preparation and storage of metallic sodium requires a strict oxygen-free and water-free environment, and the activity of metallic sodium is higher than that of metallic lithium, so it is difficult to obtain metallic sodium powder that can be stably stored. The electrochemical pre-sodium method has two significant advantages: first, the degree of pre-sodium can be accurately controlled by adjusting the discharge cut-off voltage; second, the SEI film formed by this method is relatively uniform and stable. However, the complex process of assembling half-cells-disassembly-reorganization greatly reduces the feasibility of the electrochemical pre-sodium method in large-scale production, which seriously hinders the commercialization of this method. Therefore, the development of a new carbon negative electrode treatment method that ensures the improvement of the reversible capacity of the battery while having the advantage of simple process is crucial to the commercial application of sodium-ion batteries. Improvement measures for repairing carbon-based negative electrode defects and improving the first efficiency and cycle life have attracted many researchers.

[0004] Researchers have tried to use a sodium supplement instead of metallic sodium, which can complete the pre-sodiumization of the hard carbon negative electrode in a short time. According to the Chinese invention patent document CN 109546134 A, in order to improve the first-week coulomb efficiency of the sodium-ion battery negative electrode, the invention reacts the sodium-ion battery negative electrode material with an aromatic sodium solution. The obtained pre-sodiumized hard carbon negative electrode material has a first-week coulomb efficiency compared to the negative electrode that has not been pre-sodiumized. It is increased from 60.5% to 95.8%. In the document ACS Appl. Mater. Inter. 2020, 10, 15751-15759, researchers developed a sodium biphenyl negative electrode sodium supplement to replace sodium metal. The ICE value of the pre-sodiumized sodium negative electrode was increased from 70% to 99.9% at a current density of 20mA / g. In the document Adv.Energy.Mater.2023,13,2300776, researchers reported a NaBH4 sodium supplement thermal decomposition pre-precipitation strategy. The thermal decomposition of NaBH4 produces metallic sodium on the hard carbon surface to compensate for the loss of sodium during the first charge and discharge process. The pretreatment increased the ICE of hard carbon from 83% to 99%. Although the above-mentioned sodium supplement pre-sodium method can alleviate the problem of low coulomb efficiency of hard carbon negative electrode in the first week, this strategy still makes it difficult to suppress the side decomposition reaction of electrolyte on the carbon surface, which is not conducive to the long-cycle stability of sodium ion batteries. At the same time, the residual problem of sodium supplement and organic solvent in the electrode is also difficult to avoid, and its influence on the electrochemical performance of the electrode needs further study. Summary of the invention

[0005] In order to solve the problems of low first-week coulombic efficiency and poor cycle stability caused by the trap effect caused by defects in carbon-based materials and the solid electrolyte interface that produces irreversible capacity, the present invention provides a defect repair and stabilization strategy for carbon-based sodium storage materials, which supplements the irreversible sodium loss at the defects. At the same time, the semi-metallic sodium produced at the intrinsic defects of the carbon-based sodium storage materials can induce the formation of SEI film on the surface of the carbon-based negative electrode. On the other hand, the carbonyl C=O (carbonyl) bond is accurately implanted as the active center through the self-polymerization reaction of dopamine salt on the surface of the carbon-based negative electrode, which can controllably catalyze the preferential reduction of salts and directionally guide the growth of SEI to form a uniform and dense SEI, which inhibits the decomposition reaction of the electrolyte on the surface of the carbon-based negative electrode. Thanks to this defect repair and stabilization strategy, the first-week coulombic efficiency of the treated carbon-based negative electrode has been significantly improved, and the uniform and dense SEI inhibits the secondary decomposition reaction of the electrolyte on the carbon surface, thereby realizing the practical development of a long-life sodium-ion battery system.

[0006] Specifically, the present invention provides a method for defect repair and stabilization of a carbon-based sodium storage material, wherein the carbon-based sodium storage material or a negative electrode containing the carbon-based sodium storage material is first reacted with an aromatic ketone sodium solution, then reacted with a dopamine salt solution for a second time, and finally washed and dried to obtain a modified carbon-based sodium storage material or a modified negative electrode containing the carbon-based sodium storage material.

[0007] Preferably, the negative electrode prepared with the carbon-based sodium storage material comprises: a current collector, and an active material layer coated on the surface of the current collector; the active material layer comprises the carbon-based sodium storage material, a conductive agent and a binder; The carbon-based sodium storage material comprises: a composite of one or at least two of a hard carbon material, a soft carbon material and a graphite material; Preferably, the components of the active material layer include: 70 to 99 parts of carbon-based sodium storage material, 0.5 to 10 parts of conductive agent, and 0.5 to 10 parts of adhesive; Preferably, the binder is selected from at least one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), transparent polyamide (PAMAC), polyvinyl alcohol (PVA) and sodium alginate.

[0008] Preferably, the hard carbon material includes at least one of resin carbon, biomass carbon, organic pyrolysis carbon and carbon black; The soft carbon material comprises at least one of petroleum coke, needle coke and carbon fiber; The graphite material includes at least one of expanded graphite, mesophase carbon microbeads, natural graphite and composite graphite.

[0009] Preferably, the solute of the aromatic ketone sodium solution is aromatic ketone and its derivative sodium, and the solvent is an aprotic solvent; The concentration of the solute in the aromatic ketone sodium solution is 0.05-5 mol / L.

[0010] Preferably, the solute of the aromatic ketone sodium solution includes at least one of sodium oxybenzone, sodium benzophenone, sodium benzil, sodium anthrone, sodium p-hydroxyacetophenone, and sodium tetralone; The aprotic solvent includes at least one of diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, methyl tert-butyl ether, dioxolane, N,N-dimethylformamide and dimethyl sulfoxide.

[0011] Preferably, the solute of the dopamine salt solution is dopamine salt, and the solvent is tris(hydroxymethyl)aminomethane-hydrochloric acid buffer; the concentration of the solute in the dopamine salt solution is 0.5-5 mg / mL.

[0012] Preferably, the dopamine salt includes at least one of dopamine formate, dopamine acetate, dopamine propionate, dopamine malate, dopamine lactate, dopamine citrate, and dopamine ascorbate; Preferably, the components of the Tris(hydroxymethyl)aminomethane-hydrochloric acid buffer include Tris(hydroxymethyl)aminomethane, water and hydrochloric acid, wherein the molar concentration of Tris(hydroxymethyl)aminomethane is 10 mM and the pH value is 8.5.

[0013] Preferably, the carbon-based sodium storage material reacts with the aromatic ketone sodium solution by coating the aromatic ketone sodium solution on the surface of the carbon-based sodium storage material or the negative electrode prepared containing the carbon-based sodium storage material, or immersing the carbon-based sodium storage material or the negative electrode prepared containing the carbon-based sodium storage material in the aromatic ketone sodium solution; The method for reacting the carbon-based sodium storage material with the dopamine salt solution includes: coating the dopamine salt solution on the surface of the carbon-based sodium storage material that has undergone a single reaction or the negative electrode prepared from the carbon-based sodium storage material that has undergone a single reaction, or immersing the carbon-based sodium storage material that has undergone a single reaction or the negative electrode prepared from the carbon-based sodium storage material that has undergone a single reaction in the dopamine salt solution.

[0014] Preferably, the molar ratio of the carbon-based sodium storage material to the sodium in the aromatic ketone sodium solution is 1:(0.01-1000), preferably 1:(0.05-30); The molar ratio of the carbon-based sodium storage material in the negative electrode containing the carbon-based sodium storage material to the sodium in the aromatic ketone sodium solution is 1:(0.01-1000), preferably 1:(0.05-30); The molar ratio of the carbon-based sodium storage material to the dopamine salt in the dopamine salt solution is 1:(0.01-1000), preferably 1:(0.1-20); The molar ratio of the carbon-based sodium storage material in the negative electrode containing the carbon-based sodium storage material to the dopamine salt in the dopamine salt solution is 1:(0.01-1000), preferably 1:(0.1-20).

[0015] Preferably, the temperature of the primary reaction is 20-60°C, and the reaction time is 5min-72h; The temperature of the secondary reaction is 20-60° C., and the reaction time is 1 min-48 h.

[0016] In a second aspect, the present invention provides a modified carbon-based sodium storage material prepared according to the above-mentioned defect repair and stabilization method.

[0017] In a third aspect, the present invention provides a modified negative electrode containing a carbon-based sodium storage material prepared according to the defect repair and stabilization method described above.

[0018] In a fourth aspect, the present invention provides a sodium ion battery, characterized in that it comprises: the above-mentioned modified carbon-based sodium storage material as a negative electrode active material or the above-mentioned modified negative electrode containing a carbon-based sodium storage material.

[0019] Beneficial effects of the present invention: In the present invention, mild aromatic ketone sodium and safe and non-toxic dopamine salt are selected to repair and stabilize the carbon-based sodium storage material, which can compensate for the irreversible absorption of Na by impurity defects, react with carbon defects to form quasi-metallic sodium, and use dopamine salt to reconstruct the surface function of the carbon-based negative electrode, controllably implant carbonyl active sites, controllably catalyze the preferential reduction of salts, and directionally guide the growth of the solid electrolyte interface (SEI) to form a uniform and dense SEI, inhibit the decomposition side reaction of the electrolyte on the negative electrode surface, and significantly improve the first week coulomb efficiency and cycle stability of the carbon-based negative electrode. And the method has a simple operation process, strong safety, and is easy to industrialize. At the same time, matching the defect-repaired and stabilized negative electrode with the positive electrode can promote the improvement of the energy density and cycle stability of the full battery, and promote the industrialization process of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The first week charge and discharge curve of the hard carbon negative electrode before and after defect repair and stabilization of Example 1 is shown in the figure. It can be seen from the figure that the discharge specific capacity of the hard carbon negative electrode of Example 1 after treatment can reach 350mAh / g, and the coulomb efficiency can reach 100%. The discharge specific capacity of the hard carbon negative electrode before treatment can reach 505mAh / g, and the coulomb efficiency is 69%; Figure 2 This is a long-term cycle stability diagram of the hard carbon electrode after defect repair and stabilization treatment in Example 1. It can be seen from the figure that the specific capacity retention rate of the treated hard carbon electrode after 1000 cycles is 95.4%; Figure 3 The first week charge and discharge curve of the soft carbon negative electrode after defect repair and stabilization of Example 2 is shown in the figure. It can be seen from the figure that the discharge specific capacity of the soft carbon negative electrode of Example 2 after treatment can reach 230 mAh / g, and the coulombic efficiency can reach 66.7%; Figure 4 The long-term cycle stability diagram of the soft carbon electrode after defect repair and stabilization treatment in Example 2. It can be seen from the figure that the specific capacity retention rate of the treated soft carbon electrode after 1000 cycles is 85.8%; Figure 5 The first week charge-discharge curve of the expanded graphite negative electrode after defect repair and stabilization of Example 3 is shown in the figure. It can be seen from the figure that the discharge specific capacity of the expanded graphite negative electrode of Example 3 after treatment can reach 174.8 mAh / g, and the coulombic efficiency can reach 79%; Figure 6 This is a long-term cycle stability diagram of the defect-repaired and stabilized expanded graphite electrode of Example 3. It can be seen from the figure that the specific capacity retention rate of the treated expanded graphite electrode after 1000 cycles is 88.3%; Figure 7The first week charge and discharge curve of the hard carbon negative electrode after defect repair and stabilization of comparative example 1. It can be seen from the figure that the discharge specific capacity of the hard carbon negative electrode of Example 1 after treatment can reach 323 mAh / g, and the coulombic efficiency can reach 96.9%; Figure 8 The long-term cycle stability diagram of the hard carbon electrode after defect repair and stabilization treatment of comparative example 1 shows that the specific capacity retention rate of the treated hard carbon electrode after 1000 cycles is 81%; Fig. 9 The first week charge and discharge curve of the hard carbon negative electrode of comparative example 2 after defect repair and stabilization. It can be seen from the figure that the discharge specific capacity of the hard carbon negative electrode of comparative example 2 after treatment can reach 337 mAh / g, and the coulomb efficiency can reach 90%; Fig.10 The long-term cycle stability diagram of the hard carbon electrode after defect repair and stabilization treatment of comparative example 2, from which it can be seen that the specific capacity retention rate of the treated hard carbon electrode after 1000 cycles is 76%; Fig.11 This is a first-week charge and discharge curve diagram of the sodium ion full battery assembled before and after the hard carbon electrode defect repair and stabilization treatment of Example 1. It can be seen from the figure that the discharge process shows two voltage platforms, and the discharge specific capacity of the sodium ion full battery assembled with the treated hard carbon electrode can reach 138mAh / g, which is significantly improved compared to the discharge specific capacity before treatment. DETAILED DESCRIPTION

[0021] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0022] In the present disclosure, a carbon-based sodium storage material or a negative electrode containing a carbon-based sodium storage material is first reacted with an aromatic ketone sodium solution. After one washing and one drying, the reacted carbon-based negative electrode is then immersed in a dopamine salt solution, and the dopamine salt undergoes a spontaneous polymerization reaction on the surface of the carbon-based negative electrode to form polydopamine on the surface. Finally, after a second washing and a second drying, a defect-repaired and stabilized carbon-based sodium storage material or negative electrode can be obtained.

[0023] The reaction of the carbon-based negative electrode of the sodium ion battery with the sodium aromatic ketone solution can compensate for the irreversible absorption of Na by impurity defects and react with carbon defects to form semi-metallic sodium. Dopamine salt is then used to reconstruct the surface function of the carbon-based negative electrode, controllably implant carbonyl active sites, controllably catalyze the preferential reduction of salts, and directionally guide the growth of the solid electrolyte interface (SEI) to form a uniform and dense SEI, inhibit the decomposition side reaction of the electrolyte on the negative electrode surface, and significantly improve the first-week coulomb efficiency and cycle stability of the carbon-based negative electrode.

[0024] In an optional embodiment, the solute of the aromatic ketone sodium solution is aromatic ketone sodium, and the solvent of the aromatic ketone sodium solution is an aprotic solvent. The solute of the dopamine salt solution is dopamine salt, and the solvent of the dopamine salt solution is tris(hydroxymethyl)aminomethane-acid buffer.

[0025] In an optional embodiment, the carbon-based sodium storage material includes a negative electrode active material or a negative electrode plate, and the battery negative electrode material reacts with the aromatic ketone sodium solution in a manner that includes: immersing the negative electrode material in the aromatic ketone sodium solution for a certain period of time. The reaction time of the aromatic ketone sodium solution and the negative electrode material is 5 min to 72 h, preferably 10 min to 48 h. The reaction time of the dopamine salt solution and the negative electrode material is 1 min to 48 h, preferably 5 min to 24 h.

[0026] In an optional embodiment, the negative electrode plate includes the following components in parts by weight: 70 to 99 parts of negative electrode active material, 0.5 to 10 parts of conductive agent, and 0.5 to 10 parts of binder. The conductive agent is acetylene black, Ketjen black, Super P, or one or more of the above materials. The binder is PVDF, CMC, PAA, or one or more of the above materials. Preferably, the negative electrode active material of the sodium ion battery includes: a composite of one or more of hard carbon material, soft carbon material, and graphite.

[0027] In an optional embodiment, the molar ratio of the negative electrode active material to the sodium in the aromatic ketone sodium solution during the reaction is 1:(0.01-1000), preferably 1:(0.05-30). The molar ratio of the negative electrode active material to the dopamine salt in the dopamine salt solution during the reaction is 1:(0.01-1000), preferably 1:(0.1-20).

[0028] In an optional embodiment, the solute of the aromatic ketone sodium solution is any one or more of sodium oxybenzone, sodium benzophenone, sodium benzil, sodium anthrone, sodium p-hydroxyacetophenone, and tetralone. The concentration of the solute in the aromatic ketone sodium solution is 0.001-10 mol / L, and more preferably 0.05-5 mol / L. The solute of the dopamine salt solution is any one or more of dopamine formate, dopamine acetate, dopamine propionate, dopamine malate, dopamine lactate, dopamine citrate, and dopamine ascorbate, and the concentration of the solute in the dopamine salt solution is 0.1-10 mg / mL, and more preferably 0.5-5 mg / mL. The solvent of the sodium aromatic ketone solution is any one or more of ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, methyl tert-butyl ether, dioxolane, N,N-dimethylformamide, and dimethyl sulfoxide. The solvent of the dopamine salt solution is tris (hydroxymethyl) aminomethane-hydrochloric acid buffer (Tris-HCl) with a molar concentration of 10 mM and a pH value of 8.5.

[0029] In the present disclosure, a sodium ion battery, whose negative electrode material adopts the defect repair and stabilized negative electrode material prepared by the above method, includes a defect repair and stabilized battery negative electrode, a sodium ion battery positive electrode, a separator, and an electrolyte. Its positive electrode can be one or more of a sodium-based transition metal oxide (such as sodium cobaltate, sodium manganate, sodium ferrite, etc.), a sodium-based transition metal phosphate (such as sodium iron phosphate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron pyrophosphate, etc.), and a sodium-based transition metal cyanide compound (such as sodium ferrocyanide, Prussian blue compounds, etc.).

[0030] This method can be carried out at room temperature and pressure, the process is simple and feasible, the degree of defect repair is controllable, and it is very suitable for large-scale applications. The energy density and cycle stability of the sodium-ion full battery assembled by matching the carbon-based negative electrode with the sodium storage positive electrode after defect repair and stabilization treatment have been significantly improved, thereby promoting the practical development of long-life sodium-ion battery systems.

[0031] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0032] Example 1 The slurry containing 80% hard carbon, 10% super P and 10% carboxymethyl cellulose was coated on aluminum foil to prepare a hard carbon negative electrode. After drying at 90 °C for 10 h, the electrode film was punched into a pole piece with a diameter of 12 mm. The mass loading of the active material was about 2.5 mg cm -2 . Equimolar amounts of oxybenzone and metallic sodium were mixed and dissolved in diethylene glycol dimethyl ether solvent to prepare a 0.5 mol / L sodium oxybenzone solution. The hard carbon electrode was immersed in 10 mL of sodium oxybenzone solution and reacted for 30 min under inert atmosphere. After washing and drying, the electrode was immersed in 100 mL of dopamine solution, stirred at room temperature for 60 min, and then washed and dried to obtain a defect-repaired and stabilized hard carbon negative electrode. For the half-cell, sodium foil, 1.0 M NaPF6 in diethylene glycol dimethyl ether solution and glass fiber filter paper were used as the counter electrode, electrolyte and diaphragm, respectively. The button cell (CR2032) was assembled in an argon-filled glove box and electrochemically tested after standing for 6 hours. Figure 1The first-week charge-discharge curves of the hard carbon negative electrode before and after defect repair and stabilization treatment are compared. As can be seen from the figure, the first-week efficiency of the untreated hard carbon negative electrode is only 69%, and the first-week efficiency is significantly improved to 99.9% after defect repair and stabilization treatment. Figure 2 The long-term cycle stability of the hard carbon negative electrode after defect repair and stabilization treatment has a capacity retention rate of 95.4%, indicating that defect repair and stabilization treatment have a significant improvement effect on the cycle stability of the electrode material.

[0033] Example 2 The soft carbon anode was prepared by coating a slurry containing 80% soft carbon, 10% super P and 10% carboxymethyl cellulose on aluminum foil. After drying at 90 °C for 10 h, the electrode film was punched into a 12 mm diameter electrode sheet. The mass loading of the active material was about 2.5 mg cm -2 . Equimolar amounts of oxybenzone and metallic sodium were mixed and dissolved in diethylene glycol dimethyl ether solvent to prepare a 0.5 mol / L sodium oxybenzone solution. The soft carbon electrode was immersed in 10 mL of sodium oxybenzone solution and reacted for 30 min under inert atmosphere. After washing and drying, the electrode was immersed in 100 mL of dopamine solution, stirred at room temperature for 60 min, and then washed and dried to obtain a defect-repaired and stabilized soft carbon negative electrode. For the half-cell, sodium foil, 1.0 M NaPF6 diethylene glycol dimethyl ether solution and glass fiber filter paper were used as the counter electrode, electrolyte and diaphragm, respectively. The button cell (CR2032) was assembled in an argon-filled glove box and electrochemically tested after standing for 6 hours. Table 1 compares the first-week charge and discharge coulomb efficiency and capacity retention rate after 1000 cycles of the soft carbon negative electrode before and after defect repair and stabilization treatment.

[0034] Example 3 The expanded graphite anode was prepared by coating a slurry containing 80% expanded graphite, 10% super P and 10% carboxymethyl cellulose on aluminum foil. After drying at 90 °C for 10 h, the electrode film was punched into a 12 mm diameter electrode sheet. The mass loading of the active material was about 2.5 mg cm -2. Equimolar amounts of oxybenzone and metallic sodium were mixed and dissolved in diethylene glycol dimethyl ether solvent to prepare a 0.5 mol / L sodium oxybenzone solution. The expanded graphite electrode was immersed in 10 mL of sodium oxybenzone solution and reacted for 30 min under inert atmosphere. After washing and drying, the electrode was immersed in 100 mL of dopamine solution, stirred at room temperature for 60 min, and then washed and dried to obtain a defect-repaired and stabilized graphite negative electrode. For the half-cell, sodium foil, 1.0 M NaPF6 diethylene glycol dimethyl ether solution and glass fiber filter paper were used as the counter electrode, electrolyte and diaphragm, respectively. The button cell (CR2032) was assembled in an argon-filled glove box and electrochemically tested after standing for 6 hours. Table 1 compares the first-week charge and discharge coulomb efficiency and capacity retention rate after 1000 cycles of the expanded graphite negative electrode before and after defect repair and stabilization treatment.

[0035] Example 4 The negative electrode prepared above was matched with the commonly used sodium storage positive electrode sodium manganese phosphate to assemble into a sodium ion full battery, and the effects of defect repair and stabilization treatment on the positive and negative electrode matching, capacity utilization, coulombic efficiency and cycle stability of the full battery were evaluated. Table 1 compares the electrochemical properties of several negative electrodes. As can be seen from the table, the defect repair and stabilization treatment of the electrode effectively improved the first-week coulombic efficiency of the negative electrode, and the long-term cycle stability was also improved to a certain extent.

[0036] Comparative Example 1 The slurry containing 80% hard carbon, 10% super P and 10% carboxymethyl cellulose was coated on aluminum foil to prepare a hard carbon negative electrode. After drying at 90 °C for 10 h, the electrode film was punched into a pole piece with a diameter of 12 mm. The mass loading of the active material was about 2.5 mg cm -2 . Equimolar amounts of oxybenzone and metallic sodium were mixed and dissolved in diethylene glycol dimethyl ether solvent to prepare a 0.5 mol / L sodium oxybenzone solution. The hard carbon electrode was immersed in 10 mL of the sodium oxybenzone solution and reacted for 30 min under the protection of an inert atmosphere. For the half-cell, sodium foil, 1.0 M NaPF6 solution in diethylene glycol dimethyl ether and glass fiber filter paper were used as the counter electrode, electrolyte and diaphragm, respectively. The button cell (CR2032) was assembled in an argon-filled glove box and electrochemically tested after standing for 6 hours.

[0037] Comparative Example 2 The slurry containing 80% hard carbon, 10% super P and 10% carboxymethyl cellulose was coated on aluminum foil to prepare a hard carbon negative electrode. After drying at 90 °C for 10 h, the electrode film was punched into a pole piece with a diameter of 12 mm. The mass loading of the active material was about 2.5 mg cm -2. The electrode was directly immersed in 100 mL of dopamine solution, stirred at room temperature for 60 min, washed and dried to obtain the defect-repaired and stabilized hard carbon negative electrode. For the half-cell, sodium foil, 1.0 M NaPF6 diethylene glycol dimethyl ether solution and glass fiber filter paper were used as the counter electrode, electrolyte and diaphragm, respectively. The button cell (CR2032) was assembled in an argon-filled glove box and electrochemically tested after standing for 6 hours.

[0038] Table 1 shows the performance comparison of sodium ion full batteries assembled with defect repair and stabilization treatment anodes

[0039] In summary, the method of using aromatic ketone sodium reagents and dopamine salts to implant carbonyl active centers to repair defects and stabilize carbon-based sodium storage materials is effective, easy to operate, and highly safe, and can significantly improve the first-week coulombic efficiency and long-term cycle stability of the carbon-based negative electrode of sodium ion batteries. When the electrodes treated by this method are matched into a full battery, a full battery with high first-week efficiency and high energy density can be obtained, which has high research prospects and application value.

[0040] The embodiments described above are only preferred examples of the present invention and are not intended to limit the present invention in any form. There are other variations and modifications without exceeding the technical solutions described in the claims.

Claims

1. A defect repair and stabilization method for a carbon-based sodium storage material, characterized in that: The carbon-based sodium storage material or the negative electrode containing the carbon-based sodium storage material is first reacted with an aromatic ketone sodium solution, then reacted with a dopamine salt solution for a second time, and finally washed and dried to obtain a modified carbon-based sodium storage material or a modified negative electrode containing the carbon-based sodium storage material.

2. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 1, characterized in that: The negative electrode prepared with the carbon-based sodium storage material comprises: a current collector, and an active material layer coated on the surface of the current collector; the active material layer comprises the carbon-based sodium storage material, a conductive agent and a binder; The carbon-based sodium storage material comprises: a composite of one or at least two of a hard carbon material, a soft carbon material and a graphite material; Preferably, the components of the active material layer include: 70 to 99 parts of carbon-based sodium storage material, 0.5 to 10 parts of conductive agent, and 0.5 to 10 parts of adhesive; Preferably, the binder is selected from at least one of polyvinylidene fluoride PVDF, carboxymethyl cellulose CMC, transparent polyamide PAMAC, polyvinyl alcohol PVA and sodium alginate.

3. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 2, characterized in that: The hard carbon material comprises at least one of resin carbon, biomass carbon, organic pyrolysis carbon and carbon black; The soft carbon material comprises at least one of petroleum coke, needle coke and carbon fiber; The graphite material includes at least one of expanded graphite, mesophase carbon microbeads, natural graphite and composite graphite.

4. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 1, characterized in that: The solute of the aromatic ketone sodium solution is aromatic ketone and its derivative sodium, and the solvent is an aprotic solvent; The concentration of the solute in the aromatic ketone sodium solution is 0.05-5 mol / L.

5. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 4, characterized in that: The solute of the aromatic ketone sodium solution includes at least one of sodium oxybenzone, sodium benzophenone, sodium benzil, sodium anthrone, sodium p-hydroxyacetophenone, and sodium tetralone; The aprotic solvent includes at least one of diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, methyl tert-butyl ether, dioxolane, N,N-dimethylformamide and dimethyl sulfoxide.

6. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 1, characterized in that: The solute of the dopamine salt solution is dopamine salt, and the solvent is tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution; the concentration of the solute in the dopamine salt solution is 0.5-5 mg / mL.

7. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 6, characterized in that: The dopamine salt includes at least one of dopamine formate, dopamine acetate, dopamine propionate, dopamine malate, dopamine lactate, dopamine citrate, and dopamine ascorbate; Preferably, the components of the Tris(hydroxymethyl)aminomethane-hydrochloric acid buffer include Tris(hydroxymethyl)aminomethane, water and hydrochloric acid, wherein the molar concentration of Tris(hydroxymethyl)aminomethane is 10 mM and the pH value is 8.

5.

8. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 1, characterized in that: The method of reacting the carbon-based sodium storage material with the sodium aromatic ketone solution includes: coating the sodium aromatic ketone solution on the surface of the carbon-based sodium storage material or the negative electrode prepared containing the carbon-based sodium storage material, or immersing the carbon-based sodium storage material or the negative electrode prepared containing the carbon-based sodium storage material in the sodium aromatic ketone solution; The method for reacting the carbon-based sodium storage material with the dopamine salt solution includes: coating the dopamine salt solution on the surface of the carbon-based sodium storage material that has undergone a single reaction or the negative electrode prepared from the carbon-based sodium storage material that has undergone a single reaction, or immersing the carbon-based sodium storage material that has undergone a single reaction or the negative electrode prepared from the carbon-based sodium storage material that has undergone a single reaction in the dopamine salt solution.

9. The method for defect repair and stabilization of carbon-based sodium storage materials according to claim 1, characterized in that: The molar ratio of the carbon-based sodium storage material to the sodium in the aromatic ketone sodium solution is 1:(0.01-1000), preferably 1:(0.05-30); The molar ratio of the carbon-based sodium storage material in the negative electrode containing the carbon-based sodium storage material to the sodium in the aromatic ketone sodium solution is 1:(0.01-1000), preferably 1:(0.05-30); The molar ratio of the carbon-based sodium storage material to the dopamine salt in the dopamine salt solution is 1:(0.01-1000), preferably 1:(0.1-20); The molar ratio of the carbon-based sodium storage material in the negative electrode containing the carbon-based sodium storage material to the dopamine salt in the dopamine salt solution is 1:(0.01-1000), preferably 1:(0.1-20).

10. The method for defect repair and stabilization of a carbon-based sodium storage material according to any one of claims 1 to 9, characterized in that: The temperature of the primary reaction is 20-60°C, and the reaction time is 5min-72h; The temperature of the secondary reaction is 20-60° C., and the reaction time is 1 min-48 h.

11. A modified carbon-based sodium storage material prepared by the defect repair and stabilization method according to any one of claims 1 to 10.

12. A negative electrode containing a modified carbon-based sodium storage material prepared by the defect repair and stabilization method according to any one of claims 1 to 10.

13. A sodium ion battery, characterized in that: include: The modified carbon-based sodium storage material according to claim 11 is used as a negative electrode active material or the modified negative electrode containing a carbon-based sodium storage material according to claim 12.

Citation Information

Patent Citations

  • Sodium ion battery negative electrode pre-sodium modification method, obtained negative electrode material and sodium ion battery

    CN109546134A